Peer pressure, anxiety, and smartphone addiction among Chinese college students: a mediation analysis - Meng-Te Hung; Li-Ching Hung; Qixiang Zhou; Ziyuan Huang (BMC Psychology)
Abstract Background Smartphone addiction has become a growing concern among Chinese college students, influenced by social and emotional factors. Peer pressure is a critical environmental stressor in this context, and anxiety may serve as a psychological mechanism that explains how social influence leads to problematic smartphone use. However, limited research has explored the mediating role of anxiety in the relationship between peer pressure and smartphone addiction. Methods A total of 521 university students from Fujian, Guangdong, and Zhejiang provinces participated in an online survey. Participants completed three standardized measures: the Peer Pressure Scale, the Generalized Anxiety Disorder Scale (GAD-7), and the Smartphone Addiction Scale– Short Version (SAS-SV). bootstrap analysis was employed to examine the hypothesized mediation model. Results Peer pressure significantly predicted both anxiety and smartphone addiction. Anxiety fully mediated the relationship between peer pressure and smartphone addiction, as supported by a 95% bias-corrected bootstrap confidence interval [0.158, 0.281]. confirming the statistical robustness of the findings. Conclusion This study reveals that anxiety plays a key mediating role in the pathway from peer pressure to smartphone addiction. The findings highlight the importance of addressing emotional factors in interventions designed to reduce problematic smartphone use among university students. Mental health programs that target both peer influence and anxiety management may prove especially effective.